Efektivitas Model Flipped Classroom dengan Menggunakan Video Pembelajaran terhadap Penulisan Sandhangan Swara Aksara Jawa di SDN Denanyar 1 (International Forum of Researchers and Lecturers, 2025)
The learning of Javanese script at SDN Denanyar 1 faces significant challenges, particularly in mastering sandhangan swara. Students struggle to understand the material due to the complexity of Javanese script and the use of traditional teaching methods that are less engaging. Therefore, innovation in teaching methods is needed by implementing a flipped classroom model that utilizes instructional videos. The aim of this study is to examine the implementation of the video-based flipped classroom model and assess its effectiveness in improving the ability to write sandhangan swara in Javanese script among fourth-grade students at SDN Denanyar 1. This research uses a mixed-method approach with a one-group pretest-posttest pre-experimental design. The research stages include observation, interviews, pretest, implementation of the flipped classroom model, and posttest. The study sample consists of 30 fourth-grade students. The results indicate a significant improvement in student learning outcomes, with an average pretest score of 54% and a posttest score of 75%. Additionally, students became more motivated and proactive during the learning process, while teachers successfully created a more innovative learning environment. The conclusion of this study is that the flipped classroom model using instructional videos is effective in enhancing students' ability to write sandhangan swara in Javanese script and makes learning more interactive and enjoyable.